Paraproteinemia and Related Disorders - Ragab, Gaafar; Quartuccio, Luca.; Goubran, Hadi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents paraproteinemia and the highly complex scientific information behind it to clinicians in a way they can understand and, ultimately, apply to their diagnostic and treatment practices. Paraproteinemia or dysproteinemia is characterized by the overproduction of an immunoglobulin by clonal expansion of cells from the B cells lineage which includes the plasma cells. The resultant monoclonal protein can be composed of the entire immunoglobulin or of its components. The identification and categorization of the different representatives of this group of disorders have traveled a long distance, but despite its high prevalence there is surprisingly limited evidence, in some areas, to guide the best clinical practice both at the time of diagnosis and during follow up. This book seeks to fill that gap. The book is divided into three sections, introductory chapters, disease entities and experimental therapies. The text guides clinicians through these diseases and disorders. The group of renal diseases attributed to deposition of monoclonal immunoglobulins or their components are arranged as one disease category in order to simplify the understanding of these complicated diseases in plasma cell dysplasia. In emulation of this practical approach, at a larger scale, the volume editors and chapter authors attempt to encompass the whole spectrum of the paraproteinemias in this text. This will have the dual benefit of offering the audience a panoramic view of this group of disorders and simultaneously keeping them focused on its individual representatives. There have been many recent advances in diagnosis, risk stratifications, and management of many members of this group of diseases and they are explored in depth here. This is an ideal guide for rheumatologists, hematologists, nephrologists, immunologists, oncologists, and relevant trainees caring for patients with paraproteinemia and related disorders.
The phenomenon of Paraproteinemia -- B Cell in Health and Disease -- Immunoglobulins, structure and function -- The Bone marrow as a hotbed for Plasma Cell activation -- Animal Models in Monoclonal Immunoglobulin Related Diseases -- An Approach to The Diagnosis of Paraproteinemia -- Amyloidosis: Pathogenesis, types and diagnosis -- Amyloidosis: Clinical Manifestations and Treatment -- Primary Light Chain (AL) Amyloidosis -- Monoclonal Immunoglobulin Deposition Disease -- Multiple Myeloma -- Monoclonal Gammopathy of Undetermined Significance (MGUS) & Highlight on Monoclonal Gammopathy of Neurological Significance (MGNS) -- Monoclonal Gammopathy of Renal Significance: An Insight -- Waldenström Macroglobulinemia -- IgG4 Related Disease Overview: Pathology, Clinical picture and Treatment -- Type I cryoglobulinemia -- Paraproteinemias associated with Autoimmune Diseases -- Infections and Paraproteinemia -- Paraproteinemia In Autoinflammatory Diseases -- Paraproteins associated with malignancy -- Monoclonal Gammopathies with Miscellaneous Associations -- Novel and Experimental Clone-directed Therapies -- Non-Pharmacological Management of Paraproteinemia.
Keywords: Rheumatology; Immunology; Oncology; Rheumatology; Immunology; Oncology; Paraproteinemias